Modified Finance-Based Scheduling with Activity Splitting - Sameh Al-Shihabi; Ashraf Elazouni (Mathematics)
Construction contractors often rely on external funding to manage financial deficits caused by irregular cash inflows and outflows. To address these cash flow challenges, contractors typically adjust the start times of project activities to prevent shortages while minimizing the overall project duration. However, in severe cases, operations may need to halt if cash flow issues cannot be adequately resolved. This study introduces an alternative strategy to prevent cash shortages by allowing for the temporary suspension of activities, known as activity splitting. In this approach, operations are paused to conserve cash and then resumed when sufficient funds become available. The potential benefit of this method is illustrated through a simple, four-activity project. Extending the application to more complex projects with a set of splittable activities—each having different cash requirements, durations, and associated splitting costs—the challenge lies in identifying the optimal activities to split and determining the precise suspension and resumption times, all while minimizing or avoiding project delays and additional costs. To address this, we present a novel mixed-integer linear programming (MILP) model that optimizes the scheduling and splitting of activities to minimize project duration without breaching financial constraints. The MILP model effectively identifies the best trade-off between activity splitting and project extension, taking into account the financial and cost implications of the contractor’s constraints. This is demonstrated through a case study that considers different scenarios related to splitting costs and financial limitations.